The Impact of ICT-Integrated Learning on High School Students’ Achievement in Mathematics: A Data-Driven Analysis - Miftachurohmah, Nisa; Nasruddin, Nasruddin; Palobo, Markus (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the impact of Information and Communication Technology (ICT)-integrated learning on high school students’ mathematics achievement through a comprehensive, data-driven quantitative approach. Utilizing a correlational research design, the study involved a sample of 230 students drawn from three public high schools in Southeast Sulawesi, Indonesia. Data were obtained from two primary sources: a validated questionnaire assessing the extent and quality of ICT usage in mathematics classrooms, and students’ semester examination scores, which served as indicators of academic achievement. Descriptive statistical analysis was used to outline general patterns of ICT implementation, followed by Pearson correlation and multiple regression analyses to explore and quantify the relationship between ICT integration and student performance in mathematics. The findings demonstrate a significant positive correlation between ICT-integrated learning and students’ academic outcomes (r = 0.48, p < 0.01). Regression results further reveal that ICT usage accounts for approximately 23% of the variance in mathematics achievement, indicating a substantial contribution of technology-enhanced learning to students’ performance. These results suggest that effective incorporation of ICT tools—such as GeoGebra, Desmos, and various online learning platforms—can strengthen students’ conceptual understanding, promote deeper engagement, and facilitate more interactive learning experiences. The study underscores the importance of enhancing teachers’ digital pedagogical competencies and encourages the adoption of ICT-based instructional strategies that support active, interactive, and personalized learning within mathematics education.